The Potential Use of Rabbit Urine as a Bio Fertilizer Foliar Feed in Crop Production - Mutai, P. A. (Africa Environmental Review Journal, 2020)
An experiment was conducted in C.I.T.C Kapsabet College in Nandi Central District-Nandi County. The objective was to determine the potential use of rabbit urine as a foliar feed fertilizer in crops. Rabbit urine was collected from a gutter fitted to a slatted floor rabbit hutch and two replicate samples of concentrated urine 1000 mls each was collected and taken to National Agricultural research laboratory (NARL) - Kabete for nutrient urinalysis test. Two samples of the control (commercial foliar feed fertilizer -CF) was also taken to NARL for nutrient analysis. Other 50 mls. Samples were collected in duplicate and diluted at 0% (neat urine-F0%), 25%(F-25%) and 75%(F-75%). Two samples of the control commercial fertilizer (CF) 100 mls. were diluted at the recommended rate of 5mls. Per liter were also collected and taken to the same laboratory. Data on rabbit urine laboratory nutrient analysis results and were recorded and the results indicated that rabbit urine has better nutrients than the commercial (control-CF) fertilizer which was used in comparison, e.g. nitrogen%, phosphorus%, potassium% and calcium% were 1.05, 0.01, 0.85, 0.12 respectively and that the higher calcium levels in the rabbit urine gives better structural support to plants, hence better lodging control especially in cereals e.g.in oats as was observed in this experiment. The commercial fertilizer had N.P.K and calcium percentages of 0.70, 0.02, 0.02 and 0.002 respectively. The Ph for rabbit urine of 8.5 was Basic while commercial fertilizer was 5.0 (acidic).